ASEAN free trade agreements - Lee, Su-Hyun (2023)
ASEAN’s commitment to regional economic cooperation through trade and investment liberalization has become increasingly important amid global economic uncertainty. ASEAN’s Free Trade Agreements will continue to play a vital role in the economic prosperity and stability of the region, and in realizing ASEAN’s goal of regional economic integration.